Commensalism in yeast bacteria interactions: a study of the relationship between Metschnikowia pulcherrima and Oenococcus oeni - Barrett, Lauren Michelle (2022)
Mestrado Vinifera Euromaster - Viticulture and Enology - Instituto Superior de Agronomia